Finding Mighty - Chari, Sheela (Amulet Books : Scholastic Inc, 2017)
"Along the train lines north of New York City, twelve-year-old neighbors Myla and Peter search for the link between Myla's necklace and the disappearance of Peter's brother, Randall. Thrown into a world of parkour, graffiti, and diamond-smuggling, Myla and Peter encounter a band of thugs who are after the same thing as Randall. Can Myla and Peter find Randall before it's too late, and their shared family secrets threaten to destroy them all?"--Provided by publisher.